"This peculiar constitution of our nature": John Owen's perception of death, ontology, and the isangeloi. Issue 2 (4th March 2021) - MacPhail, Kelly
ABSTRACT: In 1680, the Puritan Congregationalist John Owen preached a sermon series called "The Christian's Work of Daily Dying, " in which he argued that dying well depended upon living well. Owen admonished Christian believers not to fear death but instead to live and die in cheer, comfort, and triumph by adhering to a daily duty of the constant exercise of faith, by having a readiness to part with the earthly body, and by adopting a wisdom that is not surprised by death's arrival. Crucially, Owen expresses an early modern reinterpretation of death by understanding it as a messenger sent by God to bring believers to Heaven and resurrect them in a new ontological category of being, as isangeloi .